2017
DOI: 10.1186/s12882-017-0708-1
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 alleviates renal fibrosis and tubular cell apoptosis through TGF-β pathway inhibition in UUO rat models

Abstract: BackgroundThymosin β4 (Tβ4) is closely associated with the cytoskeleton, inflammation, wound healing, angiogenesis, apoptosis, and myocardial regeneration, but the effects of Tβ4 treatment on chronic renal tubular interstitial fibrosis (CRTIF) are poorly known. This study aimed to examine the effects of Tβ4 on the renal apoptosis and the expression of transforming growth factor (TGF-β), E-cadherin, and α-smooth muscle actin (α-SMA) in CRTIF rat models.MethodsMale SD rats were randomized into four groups (sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Also, TGF-β can induce the activation of α-SMA in fibroblast cells, which facilitates the shrinkage of fibrotic tissues, thus leading to ischemia and hypoxia of renal tissues. 36 Besides, the activation of TGF-β1 is indicative of the occurrence of DN, and therefore, the suppressed expression of TGF-β1 and α-SMA may alleviate renal fibrosis. [37][38][39] Myofibroblast marker α-SMA can be reduced by increased expression of GAS5-AS1 to against renal fibrosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TGF-β can induce the activation of α-SMA in fibroblast cells, which facilitates the shrinkage of fibrotic tissues, thus leading to ischemia and hypoxia of renal tissues. 36 Besides, the activation of TGF-β1 is indicative of the occurrence of DN, and therefore, the suppressed expression of TGF-β1 and α-SMA may alleviate renal fibrosis. [37][38][39] Myofibroblast marker α-SMA can be reduced by increased expression of GAS5-AS1 to against renal fibrosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…4. LPS + S + BLEB or LatA or Y27632 or ML-7 or Tb4 groups: media were replaced with neutrophil supernatants 5 h after LPS treatment, cells were treated with LPS, and BLEB (10 mM) (26), LatA (1 mM) (27), Y27632 (10 mM) (26), ML-7 (10 mM) (28), or Tb4 protein (1 mg/ml) (29) was added, respectively. 5.…”
Section: Epithelial Cell and Huvec Culturementioning
confidence: 99%
“…These effects were particularly pronounced in the high dose thymosin-b4 group compared with the UUO group administered saline. 50 Overall, these studies provide evidence for an anti-fibrotic effect of thymosin-b4 in renal interstitial fibrosis through inhibition of TGF-β signalling.…”
Section: The Therapeutic Potential Of Thymosin-b4 and Its Derivativesmentioning
confidence: 74%
“…35 Another study demonstrated a beneficial effect of exogenous thymosin-b4 in the rat UUO model. 50 Adult Sprague Dawley male rats underwent UUO or sham surgery and were subsequently treated daily with 1 or 5 mg/kg thymosin-b4 or saline administered by intragastric lavage. Treatment with thymosin-b4, was shown to alleviate fibrosis assessed by light microscopy, reduce TGF-β and aSMA upregulation, restore E-Cadherin protein levels and reduce apoptosis of renal tubular cells.…”
Section: The Therapeutic Potential Of Thymosin-b4 and Its Derivativesmentioning
confidence: 99%